The potential of rosmarinic acid, carnosic acid and carnosol as antioxidants to preserve sheep (Ovis aries) sperm viability and morphological integrity - Gulyas, Jenna Lara (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.